Midwife As Change Agent: Improving HIV/AIDS Knowledge and Preventive Behaviors in Senior High School Students - Asmawati, Asmawati; Mayanti, Andi (Media Publikasi Cendekia Indonesia, 2025)
Adolescents are a vulnerable group in the spread of HIV/AIDS due to limited knowledge and a lack of accurate information. Schools, as educational institutions, play a strategic role in providing health education, with midwife positioned to act as change agents in promoting awareness and prevention of HIV/AIDS among students. This study aims to evaluate the effectiveness of midwife as change agents in improving HIV/AIDS education and prevention among senior high school students. A quasi-experimental design with a one-group pre-test and post-test approach was employed. The study involved 110 students selected through total sampling. The intervention consisted of HIV/AIDS education delivered by midwife. Data were collected using a structured questionnaire and analyzed using the Wilcoxon signed-rank test due to non-normal distribution. Results shows an increase in the median values across all variables following the intervention: the midwife role increased from a median score of 40 to 70, knowledge increased from 35 to 90, and preventive behavior increased from 35 to 80. The Wilcoxon test results indicated a statistically significant difference for all three variables before and after the intervention (ρ = 0,000 < α = 0,05). Most respondents showed improvement across all three variables, indicating the effectiveness of midwife in enhancing HIV/AIDS education and preventive actions. In conclusion, midwife serve effectively as change agents in increasing knowledge and preventive behaviors regarding HIV/AIDS among adolescents in schools. Continued collaboration between the health and education sectors is essential to sustain adolescent health initiatives.